Bangladesh Right To Information Survey 2019 - World Bank (World Bank, Washington, DC, 2020)
The year 2019 marks the tenth year of the Right to Information (RTI) act enactment in Bangladesh. The Government of Bangladesh (GoB) has made good progress in implementing the RTI Act 2009 in the past decade. The RTI survey was conducted between January and March of 2019. The survey results reveal that the contribution of the RIT Act 2009 has overall been positive in the last decade. Especially, notable progress has taken place in making the supply side prepared in implementing the RTI Act. The survey will enable policymakers and RTI activists to identify and seal the pores and bring about the desired changes in perception, behavior, and actions of various stakeholders, including the citizens.